THE EFFECT OF ONLINE LEARNING ON STUDENTS' INTEREST IN MUSIC SUBJECTS - Dani Nur Saputra; Friendska Destrigitama (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
The COVID-19 pandemic has had an impact on all sectors, including education. Learning that was initially done face-to-face has turned entirely into distance learning. Various obstacles are faced by both teachers, students, and parents. This research was conducted to determine the effect of online learning on students' interest in learning one of the subjects, namely the art of music. The research was conducted using quantitative methods. Data was collected using a questionnaire and then analyzed using one-way coefficient linear regression to determine how much influence the two variables had. The results showed that online learning affected students' interest in learning by 37.76%. At the same time, the significance value is 0.66, indicating a significant influence between the two variables.